Dupilumab combined with corticosteroid therapy for Kimura disease with multiple systemic masses: a case report and literature review - Lyu, Yansi; Cui, Yaqian; Ma, Li; Guan, Lvxin; Wen, Ziping; Huang, Jingkai; Shi, Minglan; Hou, Suchun (Frontiers in Immunology, 2024)
To date, the pathogenesis of Kimura's disease remains unclear, there is no unified diagnostic criterion, the clinical phenotype shows considerable heterogeneity, and there is a lack of optimal treatment strategies. Due to its rarity, treatment strategies for KD are still under exploration. This paper reports a case of a 37-year-old Chinese female presenting with generalized erythematous papules and pruritic eruptions for 12 years, followed by the onset of limb swellings 3 years later, ultimately diagnosed as Kimura's disease. Considering the patient's multiple lymphadenopathies and limb swellings with concurrent atopic dermatitis, the treatment regimen included initial dupilumab dosage of 600 mg (300 mg administered in two injections), followed by subcutaneous injections of 300 mg every two weeks for four months. Concurrent oral corticosteroid therapy (methylprednisolone, initial dose 16 mg/kg/day, gradually tapered with tumor regression) was also administered. Following treatment, the patient did not experience severe adverse effects, and the multiple nodules markedly decreased in size.Additionally, serum IgE levels, eosinophil, and basophil counts showed significant reductions. These results demonstrate the significant efficacy of dupilumab combined with oral corticosteroids in treating Kimura's disease with concurrent atopic dermatitis.